What Career Success Means to Student's Perspective: A Qualitative Study - Amirul Hazmi Hamdan; Mamat Supriatna; Eka Sakti Yudha (Psychocentrum Review, 2022)
Career success has different meanings for each level and condition of the person. Careers have a range at every level of life, from children, and adolescents, to adults. However, none of the studies reveals the meaning of career success at the adolescent level, such as students. Therefore, this study aims to understand the concept of career success from a student's perspective. What is the meaning of career success, and what are the characteristics of students who are successful in their careers. This research uses a qualitative case study design approach. Data were collected by face-to-face semi-structural interview technique. Participants in this study were 20 high school students (10 boys and 10 girls). Data were analyzed by the narrative analysis method. The study's results revealed that students gave meaning to career success, including objective and subjective, such as the ability to achieve self-efficacy, self-happiness and make others happy. Students' career success characteristics are grouped with abilities in knowledge, attitudes and skills. The research findings can be used to develop career success in adolescents, develop career success instruments and the purpose of career guidance and counselling services.